Techno-Economic Analysis of Solar Absorption Cooling for Commercial Buildings in India - Muthalagappan Narayanan (International Journal of Renewable Energy Development, 2017)
Space cooling and heating always tends to be a major part of the primary energy usage. By using fossil fuel electricity for these purposes, the situation becomes even worse. One of the major electricity consumptions in India is air conditioning. There are a lot of different technologies and few researchers have come up with a debate between solar absorption cooling and PV electric cooling. In a previous paper, PV electric cooling was studied and now as a continuation, this paper focuses on solar thermal absorption cooling systems and their application in commercial/office buildings in India. A typical Indian commercial building is taken for the simulation in TRNSYS. Through this simulation, the feasibility and operational strategy of the system is analysed, after which parametric study and economic analysis of the system is done. When compared with the expenses for a traditional air conditioner unit, this solar absorption cooling will take 13.6 years to pay back and will take 15.5 years to payback the price of itself and there after all the extra money are savings or profit.  Although the place chosen for this study is one of the typical tropical place in India, this payback might vary with different places, climate and the cooling demand.Article History: Received May 12th 2017; Received in revised form August 15th 2017; Accepted 1st Sept 2017; Available onlineHow to Cite This Article: Narayanan, M. (2017). Techno-Economic Analysis of Solar Absorption Cooling for Commercial Buildings in India.  International Journal of Renewable Energy Development, 6(3), 253-262.https://doi.org/10.14710/ijred.6.3.253-262